Electrode manufacturing method and electrode mixture
Patent Information
- Application Number
- JP2022505805
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-11
- Filing Date
- 2021-01-19
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-01-19
AI Technical Summary
The existing methods for manufacturing electrodes for non-aqueous electrolyte secondary batteries, such as lithium-ion batteries, face challenges with binder migration during the drying process, leading to uneven binder distribution and reduced breaking strength, especially when using dry methods that do not involve solvents.
A method involving the use of a fibrous binder formed by applying a shear force to particulate binder particles with a volume-based median diameter of 5 to 100 μm, mixed with active material and conductive materials, is used to create an electrode composite material with a solid content concentration of substantially 100%, which is then rolled into a sheet and bonded to a core material without the need for organic solvents, utilizing a pair of forming rolls with a circumferential speed ratio of 8 or more.
This approach results in an electrode composite sheet with excellent moldability and high breaking strength, eliminating the need for solvent drying and reducing labor and equipment requirements, while maintaining high electronic conductivity and formability.
Smart Images

Figure 00000008_0000 
Figure 00000009_0000 
Figure 00000009_0001
Abstract
Description
Electrode manufacturing method and electrode mixture
[0001] The present disclosure relates to an electrode manufacturing method and an electrode mixture, and more particularly to an electrode manufacturing method and an electrode mixture suitable for non-aqueous electrolyte secondary batteries such as lithium ion batteries.
[0002] Electrodes for nonaqueous electrolyte secondary batteries such as lithium-ion batteries are generally manufactured by a wet process in which an electrode mixture slurry containing an active material, a binder, and the like is applied to the surface of a metal foil core material. This process requires a drying step to volatilize and remove the solvent contained in the coating film, and there is also the problem that the binder is prone to migration during drying. When binder migration occurs, the amount of binder becomes greater on the surface side of the coating film (electrode mixture layer) than on the core material side, resulting in a bias in the binder distribution in the thickness direction of the electrode mixture layer.
[0003] In recent years, a dry method has also been proposed in which an electrode mixture sheet is produced by rolling an electrode mixture into a sheet, and the sheet is then attached to a core material to produce an electrode (see, for example, Patent Documents 1 and 2). Patent Document 1 describes the use of a composite particle powder containing an electrode active material and a binder in the production of an electrode mixture sheet. Patent Document 1 lists fluidized bed granulation and spray-drying granulation as methods for obtaining the composite particle powder. In both methods, a slurry is produced by dispersing or dissolving predetermined raw materials in a solvent, and the slurry is dried to produce a composite particle powder, which is then compressed to form a compacted powder layer.
[0004] Furthermore, it has been proposed to use a fibrillated fibrous binder in a dry method. For example, Patent Document 2 describes a method in which an active material, a particulate binder, and a conductive material are mixed using a mill, and then the mixture is subjected to high pressure and large shear force for a long period of time, thereby promoting fibrillation of the binder.
[0005] JP 2013-77560 A JP 2019-512872 A
[0006] When a slurry containing a binder is used in producing an electrode, the powdery binder is dissolved in the solvent of the slurry, causing the binder to exhibit binding properties and ensuring adhesion within the composite layer and between the composite layer and the core material. However, it is necessary to dry the solvent from the slurry, making it difficult to reduce the labor required for the process and equipment. In both the fluidized bed granulation method and the spray drying granulation method disclosed in Patent Document 1, it is necessary to dry the solvent from the slurry.
[0007] In the manufacture of electrodes by a dry method that does not use a solvent, the degree of fibrillation of the binder and the mixing state of the materials that make up the electrode mixture significantly affect the formability and breaking strength of the electrode mixture sheet. As a result of studies by the present inventors, as disclosed in Patent Document 2, it has been found that applying a large shear force to the electrode mixture for a long period of time deteriorates the formability of the electrode mixture sheet and significantly reduces the breaking strength.
[0008] The electrode composite according to the present disclosure is an electrode composite containing an active material and a fibrous binder, and is characterized in that when formed into a sheet, the break peripheral speed ratio, which is the peripheral speed ratio of a pair of forming rolls (the linear pressure of the two rolls is set to 0.03 t / cm, the gap is set to 0 μm, and the peripheral speed of one roll is set to 5 m / min) when the sheet breaks, is 8 or more.
[0009] The method for producing an electrode according to the present disclosure includes applying a shear force to a particulate binder having a volumetric median diameter of 5 to 100 μm to fibrillate it, thereby producing a fibrous binder, mixing the fibrous binder with an active material to produce an electrode mixture having a solids concentration of substantially 100%, rolling the electrode mixture into a sheet to produce an electrode mixture sheet, and bonding the electrode mixture sheet to a core material. When forming the electrode mixture into a sheet, the particulate binder is fibrillated so that the break peripheral speed ratio, which is the peripheral speed ratio of a pair of forming rolls (the linear pressure of the two rolls is set to 0.03 t / cm, the gap is set to 0 μm, and the peripheral speed of one roll is set to 5 m / min) when the sheet breaks, is 8 or greater.
[0010] According to one aspect of the present disclosure, it is possible to provide an electrode manufacturing method and an electrode mixture that are capable of producing an electrode mixture sheet that has excellent formability and high breaking strength.
[0011] Fig. 1 is a diagram showing a manufacturing process of an electrode according to an embodiment, Fig. 2 is a diagram showing a manufacturing process of an electrode according to an embodiment, and Fig. 3 is a diagram showing an electrode composite according to an embodiment.
[0012] Hereinafter, embodiments of an electrode manufacturing method and an electrode composite according to the present disclosure will be described in detail. The embodiments described below are merely examples, and the present disclosure is not limited to the following embodiments. Furthermore, the drawings referred to in the description of the embodiments are schematic, and the dimensional ratios of the components depicted in the drawings should be determined in consideration of the following description.
[0013] The electrode mixture and electrode according to the present disclosure are suitable for non-aqueous electrolyte secondary batteries such as lithium ion batteries, but can also be applied to batteries containing aqueous electrolytes or power storage devices such as capacitors. The following description will be given taking as an example an electrode mixture and electrode (particularly when applied to a positive electrode) for non-aqueous electrolyte secondary batteries.
[0014] 1 and 2 are schematic diagrams illustrating a manufacturing process for an electrode 10 according to an embodiment. As shown in FIG. 1( a), the manufacturing process for the electrode 10 involves applying shear force to a particulate binder (hereinafter referred to as "binder particles") to fibrillate it, thereby producing a fibrous binder 22 (see FIG. 3). The fibrous binder 22 is then mixed with an active material 21 (see FIG. 3) to produce an electrode mixture 20 having a solids concentration of substantially 100%. As will be described in detail later, the binder particles must have a volume-based median diameter of 5 to 100 μm. Next, as shown in FIGS. 1( b) and 2, the electrode mixture 20 is rolled into a sheet to produce an electrode mixture sheet 12, which is then bonded to a core material 11. The electrode 10 is manufactured through the above steps.
[0015] In the manufacturing process of the electrode 10, the binder particles, the active material 21, and optionally the conductive material and the like are charged into a mixer, and these materials are mixed while fibrillating the binder particles.
[0016] [Electrode] As shown in FIG. 2 , the electrode 10 includes a core material 11 and an electrode mixture sheet 12 provided on the surface of the core material 11. The electrode 10 may be a long electrode constituting a wound electrode assembly, or a rectangular electrode constituting a laminated electrode assembly. The electrode 10 is manufactured by laminating the electrode mixture sheet 12 to the core material 11 and then cutting it to a predetermined shape and dimensions. The electrode 10 can be applied to the positive electrode, the negative electrode, or both of a non-aqueous electrolyte secondary battery. However, the method for manufacturing a positive electrode according to the present disclosure does not require the use of an organic solvent as in conventional positive electrode manufacturing methods, and therefore is particularly preferred for use in the positive electrode. Eliminating the need for an organic solvent not only means that it is not necessary as a raw material, but also eliminates the need for a drying process for the organic solvent, thereby eliminating the need for exhaust equipment and the like for the drying process.
[0017] The core material 11 may be a metal foil or a film with a metal layer formed on its surface. The thickness of the core material 11 is, for example, 5 to 20 μm. In the case of a positive electrode, the core material 11 may be a metal foil whose main component is aluminum. In the case of a negative electrode, the core material 11 may be a metal foil whose main component is copper. In this specification, the term "main component" refers to the component with the highest mass ratio. The core material 11 may be an aluminum foil that is substantially 100% aluminum, or a copper foil that is substantially 100% copper.
[0018] The electrode mixture sheet 12 is provided on the surface of the core material 11 to form a mixture layer of the electrode 10. The electrode mixture sheet 12 is preferably provided on both sides of the core material 11. The electrode mixture sheet 12 includes an active material 21 and a fibrous binder 22, and has a thickness of, for example, 30 to 120 μm, preferably 50 to 100 μm. The use of the fibrous binder 22 makes it possible to roll the electrode mixture 20 into a sheet. The content of the fibrous binder 22 is preferably 0.05 to 5.0 mass% with respect to the mass of the electrode mixture sheet 12. Note that the electrode mixture sheet 12 may also include a non-fibrillated binder in addition to the fibrous binder 22.
[0019] The electrode mixture sheet 12 may contain a conductive material 23 (see FIG. 3). In particular, in the case of a positive electrode, it is preferable to use the conductive material 23 in order to improve electronic conductivity within the electrode mixture sheet 12. Examples of the conductive material 23 include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. The content of the conductive material 23 is, for example, 0.5 to 5.0 mass % with respect to the mass of the electrode mixture sheet 12. An example of the volume-based median diameter of the conductive material 23 is 0.05 to 1 μm.
[0020] The electrode mixture sheet 12 is mainly composed of an active material 21. The content of the active material 21 is preferably 85 to 99 mass %, and more preferably 90 to 98 mass %, relative to the mass of the electrode mixture sheet 12. The volume-based median diameter of the active material 21 is, for example, 1 to 30 μm, and preferably 2 to 15 μm.
[0021] The positive electrode active material 21 (positive electrode active material) generally uses a lithium transition metal composite oxide. Examples of metal elements contained in the lithium transition metal composite oxide include Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, and W. Among these, it is preferable to contain at least one of Ni, Co, and Mn. The negative electrode active material 21 (negative electrode active material) uses a carbon-based active material such as natural graphite, such as flake graphite, lump graphite, and amorphous graphite, or artificial graphite, such as lump artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). Furthermore, a Si-based active material that alloys with lithium may also be used as the negative electrode active material.
[0022] [Electrode mixture] Fig. 3 is a diagram schematically illustrating the electrode mixture 20 constituting the electrode mixture sheet 12. As shown in Fig. 3, the electrode mixture 20 includes particulate active material 21 and a fibrous binder 22, and the fibrous binder 22 adheres to the particle surfaces of the active material 21 and is entangled with the active material 21. In other words, the active material 21 is held in place by the fibrous binder 22 present in a mesh-like pattern. This type of configuration can also be confirmed in the electrode mixture sheet 12. Furthermore, when the electrode mixture 20 is a positive electrode mixture, the electrode mixture 20 preferably includes a conductive material 23.
[0023] The breaking peripheral speed ratio of the electrode mixture 20 is preferably 8 or greater. The breaking peripheral speed ratio of the electrode mixture 20 is the breaking peripheral speed ratio when a test sheet is formed to measure the breaking peripheral speed ratio. The breaking peripheral speed ratio can be measured by changing the peripheral speed ratio of a pair of forming rolls when forming a test sheet from the electrode mixture 20 and identifying the peripheral speed ratio at which the sheet breaks. The phrase "The breaking peripheral speed ratio of the electrode mixture 20 is preferably 8 or greater" means that "The breaking peripheral speed ratio when a test sheet is formed to measure the breaking peripheral speed ratio is preferably 8 or greater." When the breaking peripheral speed ratio of the electrode mixture 20 is 8 or greater, it can be determined that the binder contained in the electrode mixture 20 has been properly fibrillated. An electrode mixture 20 that satisfies this condition has excellent formability, and an electrode mixture sheet 12 with high breaking strength can be produced from the electrode mixture 20 that satisfies this condition. The breaking peripheral speed ratio is more preferably 9 or greater, and even more preferably 10 or greater.
[0024] The method for measuring the fracture peripheral speed ratio of the electrode mixture is as follows. The fracture peripheral speed ratio can be measured using an apparatus similar to the apparatus shown in FIG. 1(b) for rolling the electrode mixture into a sheet. In measuring the fracture peripheral speed ratio, the electrode mixture is rolled using two rolls to form the electrode mixture into a sheet. When forming the electrode mixture into a sheet, the linear pressure of the two constant-pressure rolls is set to approximately 0.03 t / cm, the gap is set to 0 μm, the peripheral speed of one roll is fixed to 5 m / min, and the electrode mixture is formed into a sheet while changing the peripheral speed ratio by 1 from 1 to 10. The smallest peripheral speed ratio among the peripheral speed ratios at which fracture was observed in the sheet was taken as the fracture peripheral speed ratio. The electrode mixture sheet obtained when measuring the fracture peripheral speed ratio of this electrode mixture corresponds to the test sheet described above. In this specification, the term "test sheet" can also be read as "electrode mixture sheet."
[0025] The peripheral speed ratio is the ratio of the peripheral speed of one roll to the peripheral speed of the other roll when the peripheral speed of the other roll is set to 1. The breaking peripheral speed ratio is the peripheral speed ratio at the time of breaking of the test sheet, and is the ratio of the peripheral speed of one roll to the peripheral speed of the other roll when breaking occurs in the test sheet when the peripheral speed of the other roll is set to 1. The larger the peripheral speed ratio of the two rolls, the greater the lateral shear force and the easier the test sheet is to break, so the larger the peripheral speed ratio at break, the higher the breaking strength of the sheet can be evaluated to be.
[0026] The electrode mixture 20 is preferably a mixture in which the active material 21, the fibrous binder 22, and the conductive material 23 are uniformly dispersed. The fracture peripheral speed ratio of the electrode mixture 20 is an index showing the dispersibility of the constituent materials. Furthermore, the electrode mixture 20 preferably has little particle cracking of the active material 21, and most of the conductive material 23 adheres to the particle surfaces of the active material 21, forming conductive paths between the particles. In other words, the electrode mixture 20 needs to be prepared so that particle cracking of the active material 21 is suppressed while the conductive material 23 is not taken up by the fibrous binder 22, preventing a decrease in the amount of conductive material 23 adhering to the particle surfaces of the active material 21. The manufacturing method described below makes it possible to prepare a high-quality electrode mixture 20 that satisfies these conditions.
[0027] [Electrode Manufacturing Method] The manufacturing method of the electrode 10 will be described in more detail below. Below, a manufacturing method of a positive electrode including the conductive material 23 will be exemplified, but this manufacturing method can also be applied to the manufacturing of a negative electrode. In the case of a negative electrode, a negative electrode active material is used instead of a positive electrode active material. Also, the conductive material 23 may not be added.
[0028] As shown in FIG. 1( a), the manufacturing process of the electrode 10 begins with the following steps: first, binder particles are placed in a mixer 40 and fibrillated by applying shear force. In this embodiment, an active material 21, binder particles, and a conductive material 23 are placed in the mixer 40, and these materials are mixed while fibrillating the binder particles to produce an electrode mixture 20 (hereinafter, this step will be referred to as the "first step"); next, as shown in FIG. 1( b), the electrode mixture 20 is rolled into a sheet to produce an electrode mixture sheet 12 (hereinafter, this step will be referred to as the "second step"); this manufacturing step is a dry process for manufacturing an electrode 10 using an electrode mixture 20 with a solids concentration of substantially 100%.
[0029] The dry process is described below. The dry process is a process in which active material particles and binder particles are mixed without using a solvent, i.e., the active material and binder are mixed in a state in which the solids concentration is substantially 100%. During mixing, a conductive material other than the active material and binder can be added, and even when a material other than the active material and binder is added, the solids concentration during mixing in the dry process is substantially 100%.
[0030] The binder particles are preferably particles whose main component is polytetrafluoroethylene (PTFE). PTFE is easily fibrillated and is suitable as a binder for the electrode mixture sheet 12. The binder particles may be substantially composed of PTFE alone, or may contain other components to the extent that fibrillation is not impaired. Furthermore, a binder that does not fibrillate, such as polyvinylidene fluoride (PVDF), may be used in combination with the binder particles whose main component is PTFE.
[0031] As described above, the binder particles must have a volume-based median diameter (D50) of 5 to 100 μm. In this case, prolonged mixing under high shear force is not required to uniformly disperse the active material 21, fibrous binder 22, and conductive material 23. Therefore, particle cracking of the active material 21 is suppressed, and an electrode mixture 20 can be produced in which the amount of conductive material 23 incorporated into the fibrous binder 22 is small. On the other hand, using binder particles with a D50 exceeding 100 μm requires, for example, high shear force and prolonged processing, which can lead to particle cracking of the active material 21, incorporation of the conductive material 23 into the fibrous binder 22, poor sheet formability, and reduced breaking strength. It is not practical to produce binder particles with a D50 of less than 5 μm because it is extremely difficult or can only be produced in extremely small quantities.
[0032] The D50 of the binder particles is measured using a laser diffraction particle size distribution analyzer (LA-920, manufactured by Horiba, Ltd.) with water as the dispersion medium. The D50 of the binder particles is preferably 80 μm or less, more preferably 50 μm or less, and particularly preferably 30 μm or less. The D50 can be controlled, for example, by the polymerization conditions of PTFE, or can be controlled to a range of 5 to 100 μm by crushing PTFE particles exceeding 100 μm.
[0033] In the first step, it is preferable to fibrillate the binder particles so that the breaking peripheral speed ratio of the electrode mixture 20 is 8 or more. The breaking peripheral speed ratio of the electrode mixture 20 is an index indicating the dispersibility of the constituent materials, and ultimately the formability and breaking strength of the electrode mixture sheet 12. As a result of studies by the present inventors, it has been found that using binder particles with a D50 of 5 to 100 μm and performing a mixing process with a relatively low shear force for a short period of time is extremely important for minimizing cracking of the active material, improving the dispersibility of the constituent materials, and improving the formability and breaking strength of the electrode mixture sheet 12. The breaking peripheral speed ratio of the electrode mixture 20 determines the end points of the fibrillation of the binder particles and the mixing process of the active material 21, the fibrous binder 22, and the conductive material 23.
[0034] While conventionally known devices can be used for the mixer 40, it is preferable not to use mixers that require the application of pressure using compressed air, such as jet mills. Using a jet mill increases the shear force applied to the materials, making the active material 21 more susceptible to particle cracking. If the mixing time is excessively long, the amount of conductive material 23 incorporated into the fibrous binder 22 increases. This significantly reduces the conductivity of the electrode mixture sheet, increasing its resistance and adversely affecting battery characteristics. Furthermore, if the mixing time is excessively long, the PTFE becomes too fibrous, reducing the sheet's breaking strength.
[0035] For this reason, it is preferable to use a mechanical stirring type mixer that does not require the application of pressure by compressed air as the mixer 40. Specific examples of suitable mixers 40 include devices that can apply mechanical shearing force, such as cutter mills, pin mills, bead mills, fine particle composite devices (devices in which shearing force is generated between a specially shaped rotor that rotates at high speed inside a tank and an impact plate), granulators, and kneaders such as twin-screw extrusion kneaders and planetary mixers. Among these, cutter mills, fine particle composite devices, granulators, and twin-screw extrusion kneaders are preferred. The processing time of the first step (the time during which shearing force is applied to the material) is preferably 0.5 to 10 minutes, and more preferably 1 to 5 minutes.
[0036] As shown in FIG. 1( b), in the second step, the electrode mixture 20 is rolled using two rolls 30 to form a sheet. The two rolls 30 are arranged with a predetermined gap between them and rotate in the same direction. The electrode mixture 20 is supplied to the gap between the two rolls 30, whereby the electrode mixture 20 is compressed by the two rolls 30 and stretched into a sheet. The two rolls 30 have, for example, the same roll diameter. The obtained electrode mixture sheet 12 may be passed through the gap between the two rolls 30 multiple times, or may be stretched one or more times using other rolls with different roll diameters, peripheral speeds, gaps, etc. Alternatively, the rolls may be heated to heat-press the electrode mixture sheet 12.
[0037] The thickness of the electrode mixture sheet 12 can be controlled, for example, by the gap between the two rolls 30, the circumferential speed, the number of stretching treatments, etc. In the second step, it is preferable to form the electrode mixture 20 into a sheet using two rolls 30 whose circumferential speed ratio differs by at least two times. By making the circumferential speed ratio of the two rolls 30 different, for example, it becomes easier to thin the electrode mixture sheet 12, improving productivity. The circumferential speed ratio of the two rolls 30 is preferably 2.5 times or more, and may be 3 times or more. The circumferential speed ratio of the two rolls 30 is, for example, 1:3. Note that the larger the circumferential speed ratio, the greater the shear force acting on the electrode mixture sheet 12, and therefore the electrode mixture sheet 12 is required to have high breaking strength.
[0038] Next, as shown in Fig. 2, the electrode mixture sheet 12 is bonded to the core material 11 to obtain an electrode 10 in which a mixture layer made of the electrode mixture sheet 12 is provided on the surface of the core material 11 (hereinafter, this step will be referred to as the "third step"). Fig. 2 shows a state in which the electrode mixture sheet 12 is bonded to only one surface of the core material 11, but it is preferable that the electrode mixture sheet 12 is bonded to both surfaces of the core material 11. Two electrode mixture sheets 12 may be bonded to both surfaces of the core material 11 simultaneously, or one sheet may be bonded to one surface of the core material 11 and then the other sheet may be bonded to the other surface.
[0039] In the third step, the electrode mixture sheet 12 is bonded to the surface of the core material 11 using two rolls 31. The two rolls 31 have, for example, the same roll diameter, are arranged with a predetermined gap between them, and rotate in the same direction at the same peripheral speed. The two rolls 31 are preferably heated to a predetermined temperature and apply a predetermined pressure.
[0040] The electrode 10 manufactured through the above steps has a good appearance and high breaking strength, as will be shown in the examples described later.
[0041] <Examples> The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.
[0042] <Example 1> [Preparation of Positive Electrode Composite Material] Positive electrode active material (lithium transition metal composite oxide with D50 of 15 μm), PTFE particles with D50 of 9 μm, and acetylene black (D50 of 0.035 μm) were added to a mixer (Osaka Chemical, Wonder Crusher) in a mass ratio of 100:4:0.9, and mixed for 2 minutes at room temperature and a rotation speed of 14,000 rpm. This mixing process fibrillated the PTFE particles, resulting in a positive electrode composite material in which the active material, fibrous PTFE, and acetylene black were uniformly dispersed. The resulting positive electrode composite material had a solids concentration of 100%.
[0043] [Preparation of Positive Electrode Composite Sheet] The obtained positive electrode composite was passed through two rolls and rolled to prepare a positive electrode composite sheet. The peripheral speed ratio of the two rolls was set to 1:3, and the thickness of the positive electrode composite sheet was adjusted to about 100 μm.
[0044] The resulting positive electrode composites and positive electrode composite sheets were evaluated for breaking strength and film-forming properties (appearance) of the sheets by the methods described below, and the evaluation results are shown in Table 1 together with the composition of the binder particles, D50, and processing time in the mixer.
[0045] [Evaluation of Breaking Strength] Separately from the preparation of the positive electrode composite sheet, a test sheet was molded, the breaking peripheral speed ratio was measured, and the breaking strength was evaluated. The test sheet was molded by forming the positive electrode composite into a sheet as shown in FIG. 1(b), with the linear pressure of the two constant pressure rolls set to about 0.03 t / cm, the gap set to 0 μm, the peripheral speed of one roll fixed to 5 m / min, and the peripheral speed ratio changed by 1 from 1 to 10 to form the sheet. The smallest peripheral speed ratio at which breakage occurred in the sheet was taken as the breaking peripheral speed ratio, and the breaking strength of the sheet was evaluated. The breaking peripheral speed ratio was measured multiple times, and the average peripheral speed ratio of the smallest peripheral speed ratio at which breakage occurred in the sheet in each measurement was taken as the breaking peripheral speed ratio.
[0046] [Evaluation of film-forming properties] The positive electrode composite sheets obtained by the production of the positive electrode composite sheets were visually observed to evaluate the presence or absence of white streaks due to poor dispersion of the fibrous PTFE. A case in which almost no white streaks were observed and the fibrous PTFE was uniformly dispersed was rated as ◯, and a case in which there were many white streaks and there was a lot of unevenness in the fibrous PTFE was rated as ×. "A lot of white streaks and there was a lot of unevenness in the fibrous PTFE" means that the PTFE was not sufficiently fibrillated and white streaks were observed due to the presence of large PTFE particles.
[0047] Example 2 A positive electrode composite and a positive electrode composite sheet were prepared in the same manner as in Example 1, except that in preparing the positive electrode composite, PTFE particles having a D50 of 20 μm were used instead of the PTFE particles having a D50 of 9 μm, and the sheets were evaluated.
[0048] Comparative Example 1 A positive electrode composite and a positive electrode composite sheet were prepared in the same manner as in Example 1, except that in preparing the positive electrode composite, PTFE particles having a D50 of 500 μm were used instead of the PTFE particles having a D50 of 9 μm, and the sheets were evaluated.
[0049] Comparative Example 2 A positive electrode composite and a positive electrode composite sheet were prepared in the same manner as in Example 1, except that in preparing the positive electrode composite, PTFE particles having a D50 of 20 μm were used instead of the PTFE particles having a D50 of 9 μm, and the treatment time in the mixer was set to 10 minutes, and the sheets were evaluated.
[0050]
[0051] The evaluation results shown in Table 1 reveal that the positive electrode mixture sheets of the Examples all have better film-forming properties (appearance) and higher breaking strength than the positive electrode mixture sheet of Comparative Example 1. In the positive electrode mixture sheets of the Examples, the dispersibility of the active material, fibrous PTFE, and acetylene black is good, there is little particle cracking of the active material, and much of the conductive material adheres to the particle surface of the active material. Therefore, by using the positive electrode mixture sheets of the Examples, a positive electrode with excellent electronic conductivity and breaking strength can be obtained. On the other hand, the positive electrode mixture sheets of the Comparative Examples have poor material dispersibility, which results in poor film-forming properties and low breaking strength.
[0052] The breaking peripheral speed ratio of the positive electrode composite sheet of Comparative Example 2 decreased despite the use of the same binder particles as in Example 2. The breaking peripheral speed ratio also decreased despite the mixing treatment time for the positive electrode composite of Comparative Example 2 being five times longer than that for the positive electrode composite of Example 2. From the results of Comparative Example 2, it can be inferred that if the mixing time is excessively long, the PTFE becomes too fibrous, resulting in a low breaking strength.
[0053] As described above, in order to produce a high-quality electrode mixture sheet and electrode, it is necessary to use binder particles having a D50 of 5 to 100 μm in the preparation of the electrode mixture and to perform a mixing process under a relatively low shear force for a short period of time.
[0054] REFERENCE SIGNS LIST 10 Electrode 11 Core material 12 Electrode mixture sheet 20 Electrode mixture 21 Active material 22 Fibrous binder 23 Conductive material 30, 31 Roll 40 Mixer
Claims
1. An electrode mixture containing a living material and a fibrous binder, wherein when formed into a sheet, the breaking speed ratio, which is the speed ratio of a pair of forming rolls (the line pressure of the two rolls is set to 0.03 t / cm, the gap is set to 0 μm, and the peripheral speed of one roll is set to 5 m / min) when breakage occurs in the sheet, is 8 or more.
2. The electrode mixture according to claim 1, wherein the fibrous binder is mainly composed of polytetrafluoroethylene.
3. The electrode mixture according to claim 1 or 2, wherein the content of the fibrous binder is 0.05 to 5.0% by mass based on the mass of the electrode mixture.
4. A method for manufacturing an electrode, comprising producing a fibrous binder by fibrillating a particulate binder having a median diameter on a volume basis of 5 to 100 μm by applying a shearing force, mixing the fibrous binder and the living material to produce an electrode mixture having a solid content concentration of substantially 100%, fibrillating the particulate binder so that the breaking speed ratio, which is the speed ratio of a pair of forming rolls (the line pressure of the two rolls is set to 0.03 t / cm, the gap is set to 0 μm, and the peripheral speed of one roll is set to 5 m / min) when breakage occurs in the sheet formed from the electrode mixture, is 8 or more, producing an electrode mixture sheet by rolling the electrode mixture into a sheet shape, and laminating the electrode mixture sheet onto a core material.
5. The method for manufacturing an electrode according to claim 4, wherein the particulate binder is particles mainly composed of polytetrafluoroethylene.
6. The method for manufacturing an electrode according to claim 4 or 5, wherein in the step of producing the electrode mixture sheet, the electrode mixture is formed into a sheet shape using two rolls having a speed ratio different by 2 times or more.
7. The method for manufacturing an electrode according to any one of claims 4 to 6, wherein the fibrillating of the particulate binder and the mixing of the fibrous binder and the living material are performed simultaneously using a mechanical stirring type mixer that does not require pressure application by compressed air.